Socio-Economic Status of Dalits Community in Sindhuli District (Patan Pragya, 2019)
This study is based on Kamalamai Municipality, Sindhuli District. There are 56 households of Dalit (Damai 29 and Kami 27) in this area. The census method was used in the study where, total population is 365 from 56 households. Among them, 172 were male and 193 were female. The general objectives of this study are to identify demographic and socio-economic status of Dalits and to find out causes of deprivation of Dalits people in the community. They worked as agricultural labour and service work. Their income is less than their expenditure. Most of them are uneducated but nowadays, the level of education has increased so that their children go to school and college. Only 39 percent were literate and only 7 percent Dalits have passed SLC and +2. They give priority on arrange marriage. Youth generation doesn't like the traditional occupation and skills. They use a lot of alcohol (Jaad and Raski) in the festivals and rituals ceremony however the economic condition of Dalit is poor so many children of them are forced to dropout from schools because their parents cannot afford their education fees. The social status of the females in the Dalit community is very low than the males in the society. After the father's death all the properties is transferred to the son. The main causes for degrading status of Dalits are due to poverty, lack of education and lack of social awareness. So far, there have not been any kinds of policies and plans to uplift the Dalit community in this area.